2009
DOI: 10.1111/j.1442-200x.2008.02665.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of the SMN and NAIP genes in Iranian spinal muscular atrophy patients

Abstract: Deletion of the SMN1 gene is a major cause of SMA in Iran, and NAIP gene deletions were common in the present patients with type I SMA. Also, the incidence of NAIP deletion is higher in more severe SMA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 24 publications
1
15
0
1
Order By: Relevance
“…[4] Genetic diagnosis by using polymerase chain reaction (PCR)-based DNA methods have been developed to detect deletions in both SMN and Neuronal apoptosis inhibitory (NAIP) gene. [2,9] SMA is an autosomal recessive and consanguineous marriage increases the risk of the disease in the family. High prevalence of SMA has been reported in Iran, Egypt, and Saudi Arabia where consanguineous marriage rates are high.…”
Section: Resultsmentioning
confidence: 99%
“…[4] Genetic diagnosis by using polymerase chain reaction (PCR)-based DNA methods have been developed to detect deletions in both SMN and Neuronal apoptosis inhibitory (NAIP) gene. [2,9] SMA is an autosomal recessive and consanguineous marriage increases the risk of the disease in the family. High prevalence of SMA has been reported in Iran, Egypt, and Saudi Arabia where consanguineous marriage rates are high.…”
Section: Resultsmentioning
confidence: 99%
“…More than 90% of SMA patients are associated with a homozygous deletion in the SMN1 gene [7][8][9][10] . The copy number of both SMN genes varies greatly in the population.…”
Section: Introductionmentioning
confidence: 99%
“…showed the rate of SMN1 and NAIP gene deletion to be 90% and 57.3%, respectively. [26] Hasanzade et al . in 2009 analyzed deletions in exon 7 of the SMA gene only in 243 families and showed that 94% patients had deletion.…”
Section: Discussionmentioning
confidence: 99%
“…[27] A comparison of deletion frequency in survival motor neuron and neuronal apoptosis inhibitory protein genes in Iranian patients and other populations are shown in Table 2. [126303132333435]…”
Section: Discussionmentioning
confidence: 99%